Assemblies of poly(N-vinyl-2-pyrrolidone)-based double hydrophilic block copolymers triggered by lanthanide ions: characterization and evaluation of their properties as MRI contrast agents. Issue 8 (30th January 2023) - Yon, Marjorie; Gibot, Laure; Gineste, Stéphane; Laborie, Pascale; Bijani, Christian; Mingotaud, Christophe; Coutelier, Olivier; Desmoulin, Franck; Pestourie, Carine; Destarac, Mathias; Ciuculescu-Pradines, Diana; Marty, Jean-Daniel
Abstract : MRI probes based on HPICs are described. Abstract : Because of the formation of specific antibodies to poly(ethylene glycol) (PEG) leading to life-threatening side effects, there is an increasing need to develop alternatives to treatments and diagnostic methods based on PEGylated copolymers. Block copolymers comprising a poly( N -vinyl-2-pyrrolidone) (PVP) segment can be used for the design of such vectors without any PEG block. As an example, a poly(acrylic acid)- block -poly( N -vinyl-2-pyrrolidone) (PAA- b -PVP) copolymer with controlled composition and molar mass is synthesized by reversible addition–fragmentation chain transfer (RAFT) polymerization. Mixing this copolymer with lanthanide cations (Gd 3+, Eu 3+, Y 3+ ) leads to the formation of hybrid polyion complexes with increased stability, preventing the lanthanide cytotoxicity and in vitro cell penetration. These new nanocarriers exhibit enhanced T 1 MRI contrast, when intravenously administered into mice. No leaching of gadolinium ions is detected from such hybrid complexes.